Local Innovation Networking Dynamics: Evidence from South Africa. Issue 4 (September 2018) - Booyens, Irma; Hart, Tim; Ramoroka, Kgabo
Abstract The dynamics of local innovation networking are under-researched in the global South at large. While the concept of a National Innovation System (NIS) has existed in the South African policy domain for two decades, there is little, if any, empirical evidence of innovation networking at the local level. This paper interrogates the spatiality of network linkages and the networking behaviour of innovative enterprises in rural, as well as urban settings in South Africa. This research, drawn from two unrelated studies, demonstrates that innovative enterprises rely on a broad network of actors. Although local network embeddedness has a particular function, external knowledge is significant for novel innovation. A lack of local governmental support for innovation is also observed. The research provides compelling insights from the South. It is argued the notion of multi-scalar innovation networks is valid for South Africa. This is an alternative view on innovation networking in peripheral areas. La dynamique des réseaux locaux d'innovation est sous-étudiée dans l'ensemble des pays du Sud. Alors que le concept de système national d'innovation (SNI) existe dans le domaine de la politique sud-africaine depuis deux décennies, il y a peu ou pas de preuves empiriques de la mise en réseau de l'innovation au niveau local. Cet article interroge la spatialité des liens de réseau et le comportement de réseautage des entreprises innovantes dans les milieux ruraux et urbains en Afrique du Sud. Cette recherche, tirée de deux études indépendantes, démontre que les entreprises innovantes s'appuient sur un large réseau d'acteurs. Bien que l'intégration du réseau local ait une fonction particulière, les connaissances externes sont importantes pour une innovation novatrice. Un manque d'appui du gouvernement local à l'innovation est également observé. La recherche fournit des idées convaincantes en provenance des pays du Sud. On fait valoir que la notion de réseaux d'innovation multi-scalaires est valable pour l'Afrique du Sud. Ceci est une vue alternative sur le réseautage d'innovation dans les zones périphériques.